Histone Deacetylase 3 Aggravates Type 1 Diabetes Mellitus by Inhibiting Lymphocyte Apoptosis Through the microRNA-296-5p/Bcl-xl Axis - Hu, Qibo; Che, Guanghua; Yang, Yu; Xie, Hongchang; Tian, Jing (Frontiers in Genetics, 2020)
Type 1 diabetes mellitus (T1DM) is a chronic autoimmune disease characterized by immune-mediated destruction of pancreatic beta-cells. Multiple microRNAs (miRNAs) have been implicated in T1DM pathogenesis. Although histone deacetylase 3 (HDAC3) has been reported to be involved in T1DM, the underlying mechanisms remain to be further elucidated. This study was designed to investigate the potential regulatory role of Hdac3 on T1DM progression. The expression of miR-296-5p and B-cell leukemia-XL (BCL-XL) was determined using RT-qPCR and Western blot assay in peripheral blood mononuclear cells (PBMCs) of patients with T1DM, tumor necrosis factor-α (TNF-α)- and cycloheximide (CHX)-induced cell model and streptozotocin (STZ)-induced rat model. The binding affinity between miR-296-5p and Bcl-xl was verified by using dual-luciferase reporter gene assay, and the binding between Hdac3 and the promoter region of miR-296-5p was validated using chromatin immunoprecipitation assay. Western blot analysis and flow cytometry were conducted to assess the apoptotic events of lymphocytes. miR-296-5p expression was downregulated while BCL-XL expression was upregulated in PBMCs of patients with T1DM. An adverse correlation was identified between miR-296-5p and Bcl-xl in mouse TE15 B lymphocytes. Bcl-xl was further validated to be targeted and negatively regulated by miR-296-5p in 293T cells. Hdac3 inhibited miR-296-5p expression by binding to its promoter region. The effects of overexpressed Hdac3 on lymphocyte apoptosis was counterweighed via downregulation of Bcl-xl or upregulation of miR-296-5p, the mechanism of which was further validated in a rat model of DM. Taken together, the Hdac3-mediated upregulation of Bcl-xl via inhibiting miR-296-5p promoter activity enhanced the anti-apoptotic capacity of lymphocytes to accelerate the occurrence of T1DM.